Pengaruh Pelatihan, Disiplin Kerja, Fasilitas, Dan Locus Of Control Terhadap Prestasi Kerja Pegawai Di Sekolah Dasar (SD) Se-Korwil Biddik Kapanewon Paliyan Kabupaten Gunungkidul - Jajuk Herawati; Ignatius Soni Kurniawan; Briandika Choirul Azmi (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of training, work discipline, facilities, and locus of control on work performance. The population in this study were elementary school employees who were in the scope of the Regional Coordinator of Kapanewon Paliyan, Gunungkidul Regency as many as 175 employees. The sample in this study was 64 employees, the sampling technique used the slovin formula. The method of data collection in this research is to use primary data with questionnaires distributed to employees at elementary schools in Kapanewon Paliyan. The data analysis technique used descriptive analysis, classical assumption test, multiple linier regression, t test (partial), coefficient of determination (R2). The results of this study indicate that the effect of training, work discipline, and facilities partially have a positive and significant effect on work performance. While locus of control has no effect on work performance.